The Effect Of Supervision, Organizational Commitment, And Work Discipline On The Performance Of Regional Secretariat Employees Of Dharmasraya Regency - Ade Candra; Hamdy Hadi; Lusiana (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Putra Indonesia YPTK, 2021)
The purpose of this study is to find out how much influence of controlling, organization commitment, and work discipline on the employee performance of Sekretariat Daerah Kabupaten Dharmasraya. The data analysis is done by using validity test, reliability, classical assumption, multiple linear regression, F test and t test. Sampling technique by used total sampling method. The test is conducted in order to determine the effect of variables on the bound variables. Based on the results of this study found that controlling, organization climate, and work discipline have a positive and significant impact on employee performance of employees of Sekretariat Daerah Kabupaten Dharmasraya.